2011
DOI: 10.1016/j.ijadhadh.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the shear dynamic behavior of double-lap adhesively bonded joints on a wide range of strain rates

Abstract: International audienceThe main concern of this work is the mechanical characterization of adhesively bonded assemblies under dynamic shear loading ranging from quasi-static (10(-4) s(-1)) up to high (10(4) s(-1)) strain rates. The double-lap shear sample is proposed and a bonding procedure is established. The assemblies are made of steel substrates bonded with an epoxy adhesive. Two surface treatments of the substrates are considered: ethanol and sand shooting. The shear strength and the failure strain are mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 35 publications
3
22
0
1
Order By: Relevance
“…Al-Maliky et al [44] observed a pronounced drop at high strain rate while testing PEEK and polyamide-66 (PA66). Recently, Challita et al [19] reported a drop of the shear strength of adhesively bonded double-lap joints. The same adhesive, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Maliky et al [44] observed a pronounced drop at high strain rate while testing PEEK and polyamide-66 (PA66). Recently, Challita et al [19] reported a drop of the shear strength of adhesively bonded double-lap joints. The same adhesive, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [9] used the servo-hydraulic machine to study the effect of a hygrothermal exposure on the dynamic strength of adhesive joints. However, most works [10][11][12][13][14][15][16][17][18][19][20][21][22] used the split Hopkinson pressure bar technique (SHPB) to measure the dynamic strength of several types of adhesive joints: single-lap, double-lap, rod-andcollar, split-cylinder, etc. In addition to the experimental characterization, adhesively bonded joints were also investigated using numerical [23,24] and analytical [25][26][27] approaches.…”
Section: Introductionmentioning
confidence: 99%
“…There are works about the dynamic behaviour of adhesively bonded joints which give stressstrain relationships for different strain rates [7], but there are not data (at least to the knowledge of theauthors) for damage models in dynamic conditions. So the material properties are taken from [8], where their numerical results were compared with the experimental results of [9], although both works are for quasi-static loading conditions.…”
Section: Adhesive Damage Modelmentioning
confidence: 99%
“…A few research works focused on the adhesive fracture properties under dynamic loading of low to intermediate strain rate. Challita et al [6] characterized the shear behavior of assemblies at adhesive shear strain rate from 10 À 4 s À 1 to 10 4 s À 1 . The findings indicated that the fracture strain decreases and the shear strength increases with the strain rate until reaching a maximum value, and then drops back at the extremely high strain rate.…”
Section: Introductionmentioning
confidence: 99%